Monitoring temperature and smoke for substation using GSM technology / Amran Ayub - Ayub, Amran (2010)
A remote monitoring of various devices that are located in wide area is required to cut down the maintenance expenses. In industry, such monitoring system can be used among others, to control the temperature in industrial refrigerators, humidity management of biological waste disposal equipment and periodic inspection on switchboards. In other words, many unreachable parts can now be monitored if such system is implemented. The need for such system is also important for an organization or company that has several important devices that requires constant monitoring from afar as not to fully utilize the need for technical personnel to go and check due to safety reasons. Particularly if the area that need to be monitored is hazardous to health such as at waste disposal treatment area or where the area is need to be monitored without the existence of living organism such as at clean room at wafer production facility. Therefore in response to this need, it is essential to control the total system costs, including equipment maintenance to promote the remote control system. If the scope of such topic is narrowed to less demanding but yet as important as oil and gas, power generation plants areas such as universities and hospitals where the location of substations are located the remote monitoring can come in handy. Particularly when wireless application is used for data transmission and communication between two points are taken into consideration.